Rigorous simulation of nonlinear optomechanical coupling in micro- and nano-structured resonant cavities. Issue 1 (2nd January 2018) - Stocchi, Matteo; Mencarelli, Davide; Pennec, Yan; Djafari-Rouhani, Bahram; Pierantoni, Luca
Abstract: A numerical method aimed to predict the optomechanical dynamics in micro- and nano-structured resonant cavities is introduced here. The rigorousness of it is ensured by exploiting the harmonic version of the transformation optics (TO) technique and by considering all the energy-transduction contributions of electrostriction, radiation pressure, photoelasticity and moving boundaries. Since our full-wave approach implements a multi-modal analysis and also considers material losses, from both a mechanical and an optical point of view, a considerable step further has been made in respect to the standard optomechanical perturbative theory. The efficiency and the versatility of the strategy are tested by analysing the optomechanical behaviour of a corrugated Si-based nanobeam and comparing numerical results to experimental ones from the literature.